1998
DOI: 10.1007/s000180050125
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin domain boundaries in the Bithorax complex

Abstract: Eukaryotic chromosomes are thought to be organized into a series of discrete higher-order chromatin domains. This organization is believed to be important not only in the compaction of the chromatin fibre, but also in the utilization of genetic information. Critical to this model are the domain boundaries that delimit and segregate the chromosomes into units of independent gene activity. In Drosophila, such domain boundaries have been identified through two different approaches. On the one hand, elements like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 56 publications
0
85
0
Order By: Relevance
“…If the initial activation of the cis-regulatory elements in the iab regions is dependent on the intergenic transcripts, then it would be necessary not only to have unique transcription patterns within each region but also to ensure that transcription does not spread from one region to the next. Our study provides evidence that the insulators that organize the different iab regions into discrete chromatin domains (8,14,15) act to regulate the intergenic transcription program in this way.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…If the initial activation of the cis-regulatory elements in the iab regions is dependent on the intergenic transcripts, then it would be necessary not only to have unique transcription patterns within each region but also to ensure that transcription does not spread from one region to the next. Our study provides evidence that the insulators that organize the different iab regions into discrete chromatin domains (8,14,15) act to regulate the intergenic transcription program in this way.…”
Section: Discussionmentioning
confidence: 70%
“…Genetic, transgenic, and molecular studies have identified a number of classes of distinct cis-regulatory elements within the iab regions capable of directing abdA and AbdB expression. Insulator DNAs have been identified at the boundaries of the iab8-iab7 domains (Frontabdominal-8, Fab8) (4), iab7-iab6 domains (Fab7) (5)(6)(7)(8)(9)(10), and iab5-iab4 domains (Miscadastral pigmentation, Mcp) ( Fig. 1 A) (7,11).…”
Section: E Xpression Of the Abdominal-a (Abda) And Abdominal-b (Abdb)mentioning
confidence: 99%
See 2 more Smart Citations
“…Boundary elements are known to function across species 16,18,19 and Drosophila melanogaster is used as a model system of choice to study such elements from different species taking genetic and cell biology approaches in the transgenic context [20][21][22] . Before going for transgenic experiments, we checked whether GATA repeats bind to specific proteins in the Drosophila embryo nuclear extract.…”
Section: Gata Ssr Functions As Enhancer Blocker In Human Cellsmentioning
confidence: 99%